CTIM-22. NIVOLUMAB AND BEVACIZUMAB FOR RECURRENT GLIOBLASTOMA; T-CELL REACTIVITY AGAINST AUTOLOGOUS TUMOR CELLS. (12th November 2021) - Maarup, Simone; Skadborg, Signe; Borch, Annie; Draghi, Arianna; Hasselbalch, Benedikte; Østrup, Olga; Scheie, David; Skjoeth-Rasmussen, Jane; Law, Ian; Svane, Inge Marie; Poulsen, Hans; Hadrup, Sine; et al.
Abstract: INTRODUCTION: Glioblastoma is an aggressive brain tumor with a median survival of 14.6 months. We have no standard treatment for relapse and known options have limited effect. Novel treatments are necessary to improve survival and quality of life. METHODS: We present our trial; phase II open label, two-armed translational study of Nivolumab and Bevacizumab for recurrent GBM, who have failed Stupp's regimen. Patients are included in two arms depending on the possibility of salvage neurosurgical resection. Both arms receive Nivolumab and Bevacizumab administrated every second weekend, and the surgical arm also receive Nivolumab 7 days prior surgery. Forty-four patients were included by January 2021; 20 in each arm (four screen-failures). In the surgical arm, 20 fresh tumor samples as well as paired tissue from primary tumor were available. Tumor infiltrating lymphocytes (TILs) and tumor digest were produced in vitro from recurrent settings. Young TILs were expanded from fresh tumor fragments after minimal-culture, whereas rapidly expanded TILs (REP TILs) were obtained after massive expansion. By intracellular cytokine staining, we investigated the TIL reactivity after exposure to autologous tumor digest in order to evaluate whether the TILs were tumor-reactive, non-reactive or bystanders. RNA and whole exome sequencing were available before and after treatment. RESULTS: Material from 19 patients was analyzed (one out of the 20 collected biopsies was limited in size, therefore no tumor digest could be produced). Four out of 19 TIL samples showed tumor reactivity after exposure to the autologous tumor digest. Tumor reactivity was ranged between 1, 2 to 13, 6 tox% in CD8+ TILs and between 2, 8 to 10, 9 tox% in CD4+ TILs. By flowcytometry we found, IgG4+ CD3+ TILS from tumor biopsies, meaning that Nivolumab were found in the brain. Currently controls are included to evaluate these results. CONCLUSIONS: Updated results will be presented at SNO.